Business plan: a new hostel in Alentejo - Nunes, Joana Catarina Candeias (2016)
The purpose of this work is to develop a business plan which analyses the economic viability of setting up a new Hostel in Alentejo, more precisely in Sines, called Gama Hostel. Nowadays, tourism is seen as one of the leading sectors in Portugal. This happens due to the diverse options offered, as well as the specific characteristics of our country. Furthermore, Portugal has been recognized as an excellent destination for foreign tourists, mainly from Europe. However, in a context of economic crisis, as it was verified in Portugal in the last few years, and within an extremely competitive market as tourism, it becomes necessary to create innovate projects. At the same time, it is important to provide a quality service, in order to be successful in the present business environment. Therefore, it is necessary to create new services in order to meet the current customers’ needs and expectations. First, the concept of Hostel will be clarified, its main characteristics and why it is considered an interesting business opportunity. Based on this, it will be performed a complete analysis, using the most appropriate business tools, supporting the venture and exposing its differentiating factors, while keeping in mind the main goal of creating value for its customers. Following this, it will be defined the positioning and implementation policies of Gama Hostel.